Effects of flooding regime and woody bamboos on tree community dynamics in a section of tropical semideciduous forest in South-Eastern Brazil - Guilherme, FAG; Oliveira, A. T.; Appolinario, V; Bearzoti, E. (Kluwer Academic Publ, 2004)
The influence of a population of the understorey woody bamboo Merostachys riedeliana and different flooding regimes on tree community dynamics in a section of tropical semideciduous forest in South-Eastern Brazil was examined. A forest section with an area of 1.6 ha composed of 71 adjacent plots was located on a slope ending at the river margin. The section was divided into five topographical sectors according to the mean duration of river floods. In 1991 and 1998 all trees with a diameter at the base of the trunk greater than or equal to 5 cm were measured, identified and tagged, and all live bamboo culms were counted. Annualised estimates of the rates of tree mortality and recruitment, gain and loss of tree basal area, and change in bamboo density were calculated for each of the 71 plots and five topographical sectors as well as for diameter classes and tree species. To segregate patterns arising from spatially autocorrelated events, geostatistical analyses were used prior to statistical comparisons and correlations. In general, mortality rates were not compensated by recruitment rates but there was a net increase in basal area in all sectors, suggesting that the tree community as a whole was in a building phase. Tree community dynamics of the point bar forest (Depression and Levee sectors) differed from that of the upland forest (Ridgetop, Middle Slope and Lower Slope sectors) in the extremely high rates of gain in basal area. The predominant and specialised species, Inga vera and Salix humboldtiana, are probably favoured by relaxed competition in an environment stressed by long-lasting floods. In the upland forest, mortality rates were highest at the Middle Slope, particularly for smaller trees, while recruitment rates were lowest. As bamboo clumps were concentrated in this sector, the locally higher instability in the tree community probably resulted from the direct interference of bamboos. The density of bamboo culms in the upland forest was negatively correlated with the rates of tree recruitment and gain in basal area, and positively correlated with tree mortality rates. Bamboos therefore seemed to restrict the recruitment, growth and survival of trees.
Keywords: bamboo dynamics; forest turnover and stability; Merostachys; tree mortality and recruitment; Riverine forest